2016
DOI: 10.1016/j.enconman.2016.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual energy and water recovery system for self-sustained nano membrane toilet

Abstract: HighlightsEnergy and water recovery system from human excreta is modelled in Aspen Plus.The Nano Membrane Toilet is proven to be a self-sustained system.Up to 87% of total amount of water fed to the system can be recovered.Net power output of the entire system is similar to the USB port peak power (2–6 W).The specific net power output varies between 23.1 and 69.2 Wh/kgsettledsolids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…This mechanical flush -a rotating bowl and rubber swipe activated by moving the toilet lid -separates the user from a tank underneath the toilet pan (Tierney, 2014;Tierney, 2017). Solids are separated through settling and displacement, transported by an screw conveyor (Mercer et al, 2016) and subsequently dried and combusted (Fidalgo et al, 2019;Onabanjo et al, 2016), while the liquid fraction is extracted through a weir and purified through membrane processes (Kamranvand et al, 2018;Wang et al, 2017), driven by the heat of the combustion, which is transferred via a heat exchanger (Hanak et al, 2016). The toilet pedestal, including the mechanical flush, the screw conveyor, and the liquid weir are considered the NMT's front end.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanical flush -a rotating bowl and rubber swipe activated by moving the toilet lid -separates the user from a tank underneath the toilet pan (Tierney, 2014;Tierney, 2017). Solids are separated through settling and displacement, transported by an screw conveyor (Mercer et al, 2016) and subsequently dried and combusted (Fidalgo et al, 2019;Onabanjo et al, 2016), while the liquid fraction is extracted through a weir and purified through membrane processes (Kamranvand et al, 2018;Wang et al, 2017), driven by the heat of the combustion, which is transferred via a heat exchanger (Hanak et al, 2016). The toilet pedestal, including the mechanical flush, the screw conveyor, and the liquid weir are considered the NMT's front end.…”
Section: Methodsmentioning
confidence: 99%
“…The thermodynamic performance of the energy and water recovery system of the NMT unit is evaluated using a high fidelity deterministic process model, which is a revised version of the model described earlier by the authors [7] . All the processes both in the original and revised schemes were modelled in Aspen Plus simulation software (AspenTech Ltd., UK) using the thermodynamic equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…It integrates a membrane to recover clean water from urine and a compact energy conversion system to treat human faeces thermally. Recent studies confirmed that gasification and combustion are viable thermochemical technologies for the conversion of settled solids from human excreta into chemical or thermal energy [2] , [7] , [8] . Thus, the NMT has the potential to achieve self-sustained operation if energy recovery is optimised.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…An example of this approach is the Nano Membrane Toilet (NMT) which is being developed at Cranfield University as a response to the "Reinvent the Toilet Challenge" set by Bill & Melinda Gates Foundation. [5,6] The NMT includes a dryer to reduce the moisture content of HF and a micro-combustor to convert the residual solids into useful energy. The design of both stages is driven by the achievement of a complete conversion of HF into heat and flue gas as the end products and the efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%